Assessing the Energy Balance and Nutritional Needs (Macronutrients, Vitamins, Minerals) in Military Students - Sajjad Mohammadyari (طب انتظامی, 2022)
Introduction ... [1-4]. Lack of adequate nutrients may cause muscle and bone mass erosion as well as increased risk of fatigue, injury and disease [5]. In a study conducted on athletic students of Zahedan Medical University, it was found that 43.3% of people lack energy, and 6.7% lack daily protein intake [6]. Also, in the results of evaluating the nutritional status of students of Tabriz University of Medical Sciences, it has been shown that the average intake of macronutrients in male and female students is proportional to the recommended amount, but in the case of micronutrients, the average intake of vitamins B13, B6, B2, A, folacin, C and the nutrients of calcium, magnesium, and zinc in both sexes are less than the recommended amount [7]. All members of society, especially the armed forces due to stressful job tasks, should follow a proper diet that has proportionate percentages of macronutrients and micronutrients [8]. Sali et al. have examined the nutritional status of navy units [9]. The results show that the militaries in the field of nutrient intake, especially in the consumption of dairy products, vegetables, fruits, protein sources, omega 3, and sources of calcium and energy intake, need the necessary interventions to increase access and consumption of these items [9]. Klesges et al. with examining the nutritional status of 32,000 US military personnel, found that 51.7% of participants consume less than one unit of dairy products per day and only 17.9% of people consume 3 units or more of dairy products per day [10]. Also, Swain et al. in their study of soldiers showed that the consumption of milk and dairy products in soldiers is lower than in other people [11]. Aim(s) In the present study, the weekly diet of military students was examined in terms of the content and presence of macronutrients (carbohydrates, fats, proteins) and micronutrients (vitamins and minerals) and compared with their nutritional and physical needs. Research Society, Place, and Time The present study is a descriptive survey that was done in the field in 2020. The statistical population was students of a military university in Tehran with an age range of 19-24 years. Used Devices & Materials To collect the studied data, the Frequency Food Questionnaire, which has a 24-hour food recall, and also the physical activity registration questionnaire was used. Also, nutritional and physical needs, including the amounts of macronutrients, micronutrients, and calories, were determined by Food Processor N4 software according to anthropometric characteristics, existing standards, and the amount of physical, military, and sports activity of students. ... [12, 13]. The validity and reliability of the Food Frequency Questionnaire in Iran have also been reviewed and confirmed as the study of Bashir Mousavi et al. in which the validity and reliability of this questionnaire was reported as 0.86 [14]. After a public call at the university, the condition for participating in the project was mentioned. First, during a coordination session, the research objectives were identified for the volunteer subjects, and physical measurements including age, height, and weight were recorded. Each student was asked to carefully complete the forms according to the explanations provided by the researcher and the instructions provided to them. The questionnaires were then distributed among them for three days. Statistical Analysis To determine the normality of data distribution after data collection, the Shapiro-Wilk test was used. Also, to analyze the data t-test was used using SPSS 20 software with a significance level of p <0.05. Finding by Text The results of the present study showed that the mean age, height, weight, and body mass index of the participants were respectively 21.36±8.2 years, 169.64±45.10 cm, 73.34±74.6 kg, and 37.2 Kg/m2. The results of the t-test showed that the amounts of calories, energy expenditure, macronutrients, vitamins (A, D, E, B12, and C), and calcium, magnesium, and zinc were significantly different from the existing standard (p<0.05). The results obtained to compare the amount of calories received with the amount of energy expenditure required for daily physical activity based on existing standards showed that this amount was about 12% less than the estimated amount for military students (p=0.001) (Table 1). Comparing the amount of macronutrients received by the military students with the amount of energy expenditure required for daily physical activity according to the existing standards showed that the amounts of carbohydrates, fats, sodium, and vitamin K received by the samples were higher than required, while the amount of protein intake was less than the estimated need for students of the military university and was significantly different from the existing standard (p=0.001). Also, the amounts of vitamin A, D, B12, E, C, calcium, magnesium, and zinc received by students were less than the existing standards and the amounts needed to provide the necessary micronutrients for proper activities, and were significantly different from the existing standard (001/0=p) (Table 1). Main Comparison to the Similar Studies ... [15]. A study by Lutz et al. on the nutritional status of the US military has shown that macronutrient intake is optimal (except carbohydrates) [16]. This study is inconsistent with the present study. One of the reasons for this difference is the different study populations. This is because the present study examines the nutritional status of military students, while Lutz et al. studied military personnel. On the other hand, both communities have intense training activities. Carbohydrates stored in muscle and glucose in the blood are the main source of energy for very intense workouts and provide energy in the first minutes of training when there is not enough oxygen for aerobic metabolism [17]. ... [18-21]. Rostami et al. have studied the diet and satisfaction of military personnel in different areas, the results of which have reported deficiencies of vitamins A, D, B5, biotin, folic acid, and B12 in different military areas [22]. Sandstead has shown a lack of vitamins in the US military [23]. The study by Lutz et al. also showed a deficiency of micronutrients, including vitamins, in the diet of military personnel [16]. All of these studies are consistent with the present study. The only difference between the present study and the mentioned research was the recording of students' diet according to their activities, which had not been done in those studies [24]. ... [25-28]. Other findings of the present study include the lack of calcium, magnesium, and zinc intake in the samples compared to the existing standards. This finding is consistent with the study of Frank and Carty [29]. ... [30]. Without essential minerals, the delicate balance between catabolism and anabolism will be upset. Also, minerals are considered constituents of hormones [15, 31]. ... [32]. Limitations & Suggestions To reach a general conclusion and taking into account limiting factors including the study of nutrition-related factors such as race, culture as well as anthropometric factors (body fat percentage, lean body mass), blood factors (growth factors), and environmental factors (cold or tropical), it is suggested that in future studies, a comprehensive study be conducted on military students measuring all the mentioned limitations. Conclusions The amounts of calories, macronutrients (proteins), vitamins (A, D, E, B12, and C), and also the amount of calcium, magnesium, and zinc intake in the students of the military university is less than the standard amount. However, they get more carbohydrates, sodium and fat rather than the standard. Clinical & Practical Tips in Police Medicine Due to the lack of calories, macronutrients (proteins), vitamins, calcium, magnesium, and zinc, compared to the existing standards for physical activity, it seems that to protect the country, the health of the military should be an important program and their food diet should be modified according to the standards. Acknowledgments We are very grateful to all the subjects participating in the present study. Conflict of Interest The authors state that there is no conflict of interest in the present study. Funding Sources The present study had no financial support.